To determine which table shows that \( y = -f(x) \) results in a reflection over the x-axis, we need to look for a table where the values of \( -f(x) \) are the negative counterparts of the values of \( f(x) \).
Let's examine each response:
-
- For \( x = 2 \), \( f(2) = 0 \) and \( -f(2) = 0 \) (not a reflection)
- For \( x = 3 \), \( f(3) = -1 \) and \( -f(3) = 1 \) (this shows reflection)
- For \( x = 6 \), \( f(6) = -2 \) and \( -f(6) = 2 \) (this shows reflection)
-
- For \( x = 2 \), \( f(2) = 0 \) and \( -f(2) = 0 \) (not a reflection)
- For \( x = 3 \), \( f(3) = 1 \) and \( -f(3) = -1 \) (not a reflection)
- For \( x = 6 \), \( f(6) = 2 \) and \( -f(6) = -2 \) (not a reflection)
-
- For \( x = -2 \), \( f(-2) = -2 \) and \( -f(-2) = 2 \) (this shows reflection)
- For \( x = 0 \), \( f(0) = 0 \) and \( -f(0) = 0 \) (not a reflection)
- For \( x = -3 \), \( f(-3) = -1 \) and \( -f(-3) = 1 \) (this shows reflection)
- For \( x = -6 \), \( f(-6) = -2 \) and \( -f(-6) = 2 \) (this shows reflection)
-
- For \( x = -2 \), \( f(-2) = -2 \) and \( -f(-2) = 2 \) (this shows reflection)
- For \( x = 0 \), \( f(0) = 0 \) and \( -f(0) = 0 \) (not a reflection)
- For \( x = -3 \), \( f(-3) = 1 \) and \( -f(-3) = -1 \) (not a reflection)
- For \( x = -6 \), \( f(-6) = 2 \) and \( -f(-6) = -2 \) (not a reflection)
From this analysis, the first option shows the necessary reflection for \( f(3) \) and \( f(6) \), and the third option also demonstrates the reflection for points within \( f(-2) \) and \( f(-3) \).
However, because the pairs in the first response demonstrate the reflection consistently under positive values, the response that best shows that \( y = -f(x) \) corresponds to a reflection over the x-axis is:
First Response (y = -f(x)):
- For \( x = 2, -f(2) = 0 \)
- For \( x = 3, -f(3) = 1 \)
- For \( x = 6, -f(6) = 2 \)
So, I would select the first option as the answer.